2022
DOI: 10.3390/ma15196901
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking and Brushing on the Color Stability and Stainability of Different CAD/CAM Restorative Materials

Abstract: This study aimed to investigate and compare the color stability and stainability of computer-aided design/computer-aided manufacturing (CAD/CAM) restorative materials in their glazed (G) and polished (P) state when exposed to cigarette smoke, as well as after brushing. Three CAD/CAM restorative materials were investigated: lithium disilicate CAD (LD), zirconia (Zr), and Telio PMMA CAD (PMMA), according to their surface finishing and assignment to cigarette smoking exposure or soaking in the saliva (control) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, Schelkopf et al examined the effect of toothbrushing on the color stability of lithium disilicate ceramics. They noticed that a significant color change was detected in comparison with the baseline, which might be due to their testing polished ceramic surfaces without the application of a glaze layer, as performed in this study [54].…”
Section: Discussionmentioning
confidence: 55%
“…However, Schelkopf et al examined the effect of toothbrushing on the color stability of lithium disilicate ceramics. They noticed that a significant color change was detected in comparison with the baseline, which might be due to their testing polished ceramic surfaces without the application of a glaze layer, as performed in this study [54].…”
Section: Discussionmentioning
confidence: 55%
“…Their erratic color stainability and stability are some of the issues connected to the failure of cosmetic restorations. Dental plaque buildup, pigmentation from staining agents, dehydration, water absorption, surface roughness, chemical degradation, and oxidation of unreacted carbon double bonds are a few causes for color changes in resins [16].…”
Section: Discussionmentioning
confidence: 99%
“…Since the baseline L, a, and b values of the various materials differ, it is essential to assess color changes in the specimens using the ∆E values rather than the L, a, and b values obtained after aging/staining [19,32]. Furthermore, the formula for the calculation of color changes (∆E) commonly used in previous studies is dependent on values of L, a, and b.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of our study is that the effect of different finishing and polishing protocols on the stainability of ceramic restorations was neglected. The crowns were only polished, as the consensus about the association between stainability and roughness is inadequate [19]. Yuan et al reported statistically insignificant relations between stainability and roughness [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation